PENGENALAN KEAMANAN DATA, INVESTASI, DAN LITERASI KEUANGAN BAGI SISWA SEKOLAH MENENGAH KEJURUAN - Hartono, Hartono; Dewi, Siti Ratnasari; Kurniawati, Desi (Jurnal Pajak Populis, 2025)
This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to enhance the understanding and competencies of vocational high school students, particularly in digital tax accounting, data security, investment awareness, and financial literacy. The target participants were students of the Accounting and Financial Institution (AKL) major at SMK PGRI 1 Balaraja. The program employed a participatory approach consisting of three stages: preparation, implementation, and evaluation. The activities were conducted through interactive lectures, group discussions, simulations, and demonstrations of simple digital accounting applications. The results indicate a significant improvement in students’ understanding of digital tax accounting principles, awareness of data security in financial transactions, ability to identify illegal investments, and basic skills in managing personal finances using digital tools. This program proved effective in bridging the gap between theoretical learning at school and the practical competency demands of the workplace. Future programs should include continuous mentoring and the integration of financial literacy and data security materials into the vocational school curriculum to ensure long-term impact.